THOR'S CHARACTERIZATION ANALYSIS IN AVENGERS: INFINITY WAR - Jasmine Nurkamila; Dea Bella Indriani; Marudut Bernadtua Simanjuntak (Pusat Riset dan Inovasi Nasional, 2022)
The film “Avengers: Infinity War” is a film that sequel to 2012's The Avengers, and 2015's Avengers: Age of Ultron. The purpose of this study is to describe the character of one of the main characters, namely Thor and also the representation of the superhero formula from Thor. The method used in this study is a qualitative method with two research approaches, namely structural to examine the character of Thor, while the literary psychology approach uses the theory of Coogan and Cawelti about the superhero formula (protagonist). The results show that Thor has 4 characters, namely 1) Thor is the main character, 2) Thor is the protagonist, 3) Thor is a flat character, because at the beginning of the scene it is shown that Thor is grieving because of the loss of his brother, so Thor tries to take revenge from the beginning to the end of the film. 4) Thor is also a static character in the film. In the analysis of the representation of the superhero formula (protagonist), three points are obtained namely, 1) mission, 2) strength, and 3) costume. The conclusion of this study is that the superhero formula changes depending on culture, civilization, and technological sophistication.